Impacts of foraging facilitation among predators on predator-prey dynamics - Berec, Ludek (Bulletin of mathematical biology, 2010)
Whereas impacts of predator interference on predator-prey dynamics have received considerable attention, the "inverse" process-foraging facilitation among predators-have not been explored yet. Here we show, via mathematical models, that impacts of foraging facilitation on predator-prey dynamics depend on the way this process is modeled. In particular, foraging facilitation destabilizes predator-prey dynamics when it affects the encounter rate between predators and prey. By contrast, it might have a stabilizing effect if the predator handling time of prey is affected. Foraging facilitation is an Allee effect mechanism among predators and we show that for many parameters, it gives rise to a demographic Allee effect or a critical predator density in need to be crossed for predators to persist. We explore also the effects of predator interference, to make the picture "symmetric" and complete. Predator interference is shown to stabilize predator-prey dynamics once its strength is not too high, and thus corroborates results of others. On the other hand, there is a wide range of model parameters for which predator interference gives rise to three co-occurring co-existence equilibria. Such a multi-equilibrial regime is rather robust as we observe it for all the functional response types we explore. This is a previously unreported phenomenon which we show cannot occur for the Beddington-DeAngelis functional response. An interesting topic for future research thus might be to seek for general conditions on predator functional responses that would produce multiple co-existence equilibria in a predator-prey model.
Keywords: predátorské chování; populační dynamika; Predatory Behavior; Animals; Models, Theoretical; Population Dynamics; teoretické modely; zvířata; ekosystém; Ecosystem